FISIOLOGI DAYA ADAPTASI KEDELAI (Glycine max (L.) Merr.) TERHADAP CEKAMAN pH RENDAH DENGAN Al TINGGI - , Supijatno; D. Sopandie; M. Jusuf; S. Harran (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
Two AI-tolerant genotypes (KB 44001 and Genjah Jepang) and two AI-sensitive genotypes of soybean (Kedelai Lumut and KB 46015) were subjected to Al concentration (1.50 mM Al with pH 4.0) in hydroculture for 3 weeks; the growth and their physiological responses were identified by measuring the changes of pH media, NO3ˉ /NH4+ uptake, ion absorption and organic acid content in the tissues. The result revealed that Al-tolerant genotypes soybean show a much better growth than the sensitive genotypes. Moreover, the tolerant genotypes showed the different responses to Al stress; they changed the pH media more significantly, accumulated less Al in the roots and accumulated more oxalate acid than the sensitive genotypes. Both the tolerant and sensitive genotypes had similar pattern n in N03ˉ /NH4+ uptake and other cation uptake. The results suggested that tolerance of soybean genotypes to Al toxicity is associated with their ability in the exclusion AI.